Registration of Adoptions Act 1952: towards harmonisation of adoption laws governing Muslims and non-Muslims in Malaysia - Mohd, Azizah; Mohd Zin, Najibah; A.Kadir, Nadhilah; Abdul Manaf, Zati Ilham (Harun M. Hashim Law Centre, 2023)
Adoption can be simply understood as taking the child of another into a person’s custody and care as his own child. The effect of legal adoption changes the status of the adopted child from the child of one person to the child of another person. In Islam, this kind of adoption is known as ‘tabanni’ and is strictly prohibited. On the other hand, Islamic law recognised and enjoined foster parenting to provide help and assistance to children in need of protection and family, without affecting the biological status of a child. It is obvious that in the spirit of this nature of adoption and foster parenting, the law governing adoption in Malaysia was enacted to cater to the multiracial society considering both religious and cultural limitations when dealing with adoption. It follows that the Registration of Adoptions Act 1952 was enacted to govern a de facto adoption of children for both Muslims and non-Muslims. This paper seeks to examine the laws regulating adoption in Malaysia, especially under the Registration of Adoptions Act 1952 which seems to harmonise the Islamic and Civil law so as to make it applicable to both Muslims and non-Muslims. Examination extends to other laws that specifically govern the non-Muslims and the Muslims on adoption, such as the Adoption Act 1952 as well as provisions under the Islamic Family Law of the state enactments.